Pengaruh Penerapan Manajemen Risiko Terhadap Komitmen Organisasi Dalam Upaya Pencegahan Pembiayaan Bermasalah Pada Perusahaan Pt. Bina Artha Ventura - Faaris Nazaruddinsyah; Julienda Br Harahap; Bakhtiar Bakhtiar; Abd Rasyid MS (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the effect of risk management and organizational commitment on problem financing at PT. Bina Artha Ventura. The population of this study was all employees of PT. Bina Artha Ventura totaling 60 people, using saturated sampling techniques so that the entire population was sampled. Data were collected through observation and questionnaires using a Likert scale, and analyzed using multiple regression with the help of SPSS 16.0.The results of the analysis show that risk management has a positive and significant effect on problem financing. This indicates that good risk management can reduce the level of problem financing. On the other hand, organizational commitment partially does not show a positive and significant effect on problem financing. However, simultaneously, risk management and organizational commitment together have a positive and significant effect on efforts to prevent problematic financing. This finding confirms that the combination of effective risk management and strong organizational commitment contributes to reducing the risk of problematic financing. The implication of this study is the importance of synergy between comprehensive risk management and increasing employee commitment to maintain the quality of the financing portfolio in the company.